Analysis of the Income of Fiber Body Fishermen in Latuhalat Village, Nusaniwe District, Ambon City - Pattiwaellapia, Brian; Papilaya, Josef; Sahusilawane, Stevie (Universitas Pattimura, 2025)
This study aims to analyze the income of bodi fiber fishermen and the factors influencing it, such as weather, capital, technology, and fishing experience. The method used is a descriptive qualitative approach by collecting data through observation, interviews, and documentation. The results show that the income of bodi fiber fishermen tends to fluctuate, influenced by weather conditions and limited capital. Most fishermen use traditional fishing technology, such as nets, which are effective but have efficiency limitations. Experience also plays an important role, with more experienced fishermen generally having better catches. To improve fishermen's welfare, increased access to capital, modern technology, and skills training is necessary. This research provides insight into how government intervention and technical support can help improve the income and welfare of bodi fiber fishermen.